Culturally Specific Pedagogy in the Mathematics Classroom - Leonard, Jacqueline (Taylor & Francis, 2018)
Advocating for the use of culturally specific pedagogy to enhance the mathematics instruction of diverse students, this revised second edition offers a wide variety of conceptual and curricular resources for teaching mathematics in a way that combats and confronts the forms of oppression that students face today. Addressing stratification based on race, class, and gender, Leonard offers lesson templates that teachers can use with ethnically and culturally diverse students and makes the link between research and practice. Connecting cutting-edge and emerging technologies to culturally specific pedagogy, the second edition features new chapters on mathematics and social justice, robotics, and spatial visualization. Applying a more expansive focus, the new edition discusses current movements such as Black Lives Matter and incorporates examples of rural and tribal students to paint a broader picture of what culturally rich mathematics classrooms actually look like. The text builds on sociocultural theory and research on culture and mathematics cognition to extend the literature and better understand minority students' goals and learning needs. Including new discussion questions and new examples, lessons, and vignettes of integrating culture in the mathematics classroom, this book employs pedagogical research to field-test new instructional methods for culturally diverse and female students.